2015
DOI: 10.1166/jbn.2015.2078
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive Amphiphilic Methacrylic Copolymer-Functionalized Poly(<I>ε</I>-caprolactone) Nanocapsules for Nose-to-Brain Delivery of Olanzapine

Abstract: Nose-to-brain drug delivery has been proposed to overcome the low absorption of drugs in central nervous system due to the absence of brain-blood barrier in the olfactory nerve pathway. However, the presence of a mucus layer and quick clearance limit the use of this route. Herein, amphiphilic methacrylic copolymer-functionalized poly(ε-caprolactone) nanocapsules were proposed as a mucoadhesive system to deliver olanzapine after intranasal administration. In vitro evaluations showed that these nanocapsules were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Another approach was proposed by the group of Silvia Guterres and Adriana Pohlmann, who developed amphiphilic methacrylic copolymer-functionalized poly(ε-caprolactone) nanocapsules as a mucoadhesive system for N2B delivery of olanzapine, an atypical antipsychotic drug [ 88 ]. Nanocapsules showed pH-dependent size and surface charge values, ranging from 324.3 to 235.2 nm and from +55 and +22.7 mV.…”
Section: Mucoadhesive Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach was proposed by the group of Silvia Guterres and Adriana Pohlmann, who developed amphiphilic methacrylic copolymer-functionalized poly(ε-caprolactone) nanocapsules as a mucoadhesive system for N2B delivery of olanzapine, an atypical antipsychotic drug [ 88 ]. Nanocapsules showed pH-dependent size and surface charge values, ranging from 324.3 to 235.2 nm and from +55 and +22.7 mV.…”
Section: Mucoadhesive Nanoparticlesmentioning
confidence: 99%
“…Furthermore, the amphiphilic methacrylic copolymer-functionalized poly(ε-caprolactone) nanocapsules loaded with olanzapine outperformed the controls (drug solution and blank nanocapsules) also in the pre-pulse inhibition model of cognitive impairment symptoms typical of schizophrenia. Interestingly, the authors noted that brain accumulation was higher than that reported in the literature for olanzapine-loaded PLGA nanoparticles and attributed such improvement to the cationic mucoadhesive coating of the nanocapsules [ 88 ].…”
Section: Mucoadhesive Nanoparticlesmentioning
confidence: 99%
“…The mucoadhesive properties of the formulations were assessed using mucin from porcine stomach (Type II, Sigma-Aldrich, St. Louis, MO, USA) as previously described [29,50]. The mucin was dispersed in ultrapure water (0.5% w/v) and employing magnetic stirring for 3 h at room temperature.…”
Section: In Vitro Evaluation Of the Interaction Between Nanocapsules mentioning
confidence: 99%
“…As the nose is a great alternative administration route to allocate APIs directly into the CNS and provides great possibilty to take advantage of NCs, we envisage that a novel, NC formulation made with a bottom-up method could improve the interaction between the drug and the nasal epithelium. Thus the advantages of the nasal delivery and NCs could be combined [19,[51][52][53]. Therefore, the aims of this study were to design and prepare LAM-loaded chitosan NC formulations for nasal drug delivery.…”
Section: Introductionmentioning
confidence: 99%